Fear of cancer recurrence, anxiety and depressive symptoms in adolescent and young adult cancer patients - Sun H (Dove Medical Press, 2019)
Hengwen Sun,1,* Yuan Yang,2,3,* Jingying Zhang,3,* Ting Liu,3,* Hongmei Wang,4 Samradhvi Garg,5 Bin Zhang31Department of Radiotherapy, Cancer Center, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Guangzhou 510080, People’s Republic of China; 2Unit of Psychiatry, Faculty of Health Sciences, University of Macau, Macau SAR, Macau; 3Department of Psychiatry, Southern Medical University Nanfang Hospital, Guangdong-Hong Kong-Macao Greater Bay Area Center for Brian Science and Brain-Inspired Intelligence, Guangzhou, 510515, People’s Republic of China; 4Department of Radiotherapy, Southern Medical University Nanfang Hospital, Guangzhou 510515, People’s Republic of China; 5School of Health in Social Science, University of Edinburgh, Edinburgh EH8 9BL, UK*These authors contributed equally to this work Background: Previous studies have indicated that younger age is consistently associated with high levels of fear of cancer recurrence (FCR), anxiety and depression. However, the associations among these variables in adolescent and young adult (AYA) cancer patients are not clear. This study explores the prevalence and correlates of FCR, anxiety and depressive symptoms in Chinese AYA cancer population.Methods: This is a cross-sectional study that includes 249 patients aged between 15 and 39 yrs at the time of cancer diagnosis. Patient’s sociodemographic, clinical as well as psychological characteristics were collected by an information sheet, the Fear of Progression Questionnaire-Short Form (FoP-Q-SF), General Anxiety Disorder Questionnaire (GAD-7) and Patient Health Questionnaire (PHQ-9). Descriptive statistics and multivariate analyses were conducted.Results: Eighty-nine (35.74%) patients experienced dysfunctional level of FCR, eighty-two (32.93%) patients experienced anxiety symptoms and ninety-six (38.55%) reported depressive symptoms. In multivariate analyses, being single, pessimistic, having more concurrent stressful life events and physical comorbidity were independently associated with higher FCR, anxiety and depressive symptoms. Patients who were not engaging in radiotherapy were more likely to report higher anxiety level.Conclusion: FCR, anxiety and depressive symptoms are frequently reported problems among AYA cancer patients. Age-appropriate and flexible psychological interventions are needed for this high-risk population.Keywords: adolescent, anxiety, cancer, depression, fear of recurrence, young adult